DESIGNING AN ANDROID-BASED REMINDER (E-IRON) APPLICATION FOR CLASS I IMMIGRATION OFFICE TPI CIREBON - Galuh Boy Hertantyo; Gunawan Ari Nursanto; Aqbal Bagus Nafadilla (Polteknik Imigrasi, 2021)
Information Technology is a technological invention that functions to process data including processing, obtaining, compiling, storing, manipulating data in various ways to produce quality information. Forgetfulness which sometimes appears as an obstacle in carrying out office activities from employees becomes an obstacle in realizing the vision and mission of the Immigration Office Class I TPI Cirebon effectively and efficiently. The Android-Based Reminder Application (E-Iron) is a form of utilizing information technology that is used for media reminders of the implementation of scheduled work activities to employees at the Immigration Office Class I TPI Cirebon in an effort to improve employee performance in terms of punctuality. As for in this study, a discussion was carried out on system analysis and in the implementation of employee performance at the Immigration Office Class I TPI Cirebon. The creation and application of the Reminder Application (E-IRON) functions to support employee performance through reminders related to the implementation of office activities, therefore the aspect of timeliness in the implementation of the intended office activities can be carried out optimally.